Streptococcus mutans biofilm inhibition using antisense oligonucleotide to glucosyltransferases B and C - Kalesinskas, Povilas; Kačergius, Tomas; Ambrozaitis, Arvydas; Jimbo, Ryo; Ericson, Dan (Acta medica Lituanica, 2015)
Background. Biofilm formation by Streptococcus mutans bacteria on teeth leads to dental caries, which still remains one of the most prevalent human diseases strongly related to increase of dietary sucrose consumption in modern society. In the biofilm, sucrose is metabolized by S. mutans to acids causing tooth decay. S. mutans also produces glucosyltransferases (Gtfs) for synthesis of sticky glucan polymers from sucrose that provides matrix for biofilm formation on teeth. For reducing biofilm build-up, one preventive measure could be blocking of Gtf synthesis. The aim of this study was to test antisense phosphorothioate oligodeoxyribonucleotide (PS-ODN) targeting simultaneously S. mutans gtfB and gtfC mRNAs in order to inhibit biofilm formation in vitro. Materials and methods. S. mutans bacteria were grown anaerobically on glass slides inserted vertically in 24-well cell culture plates containing Todd Hewitt broth with sucrose under exposure to antisense or missense PS-ODNs at the final concentration of 10 μM. Untreated bacteria served as controls. After 24 h of incubation, glass slides were removed, air-dried and further used for the quantitative evaluation of the streptococci biofilm applying an optical profilometry technique. Results. It was revealed that antisense PS-ODN considerably reduced the most critical biofilm surface roughness parameter Sa (average difference between the peak hight and valleys) inhibiting the biofilm development by 46% and 77% in comparison to untreated (p = 0.06) and missense PS-ODN-treated bacteria (p < 0.05), respectively. Conclusions. The results demonstrate that antisense PS-ODN considerably decreases streptococci-induced biofilm development on glass slides, and might therefore significantly suppress dental biofilm formation through simultaneous inactivation of S. mutans gtfB and gtfC mRNAs.